Prevalence, antimicrobial resistance profile and comparison of methods for the isolation of salmonella in chicken liver from Argentina - Procura, Francisco; Bueno, Dante Javier; Bruno, Susana B.; Rogé, Ariel Diego (Elsevier, 2019)
This study was conducted to estimate the apparent prevalence of Salmonella spp. in chicken livers obtained from markets in Entre Ríos, Argentina, using two culture methods (preenrichment and direct selective agar plating). We also determined the antimicrobial resistance of Salmonella isolated strains and evaluated the performance of the two culture methods and selective-differential plating media used for Salmonella isolation. Of 666 chicken livers studied, 32 organs (4.8%) related to 4 poultry slaughterhouse companies were positive for Salmonella sp. using one or two culture methods. Fifty Salmonella strains were isolated from the positive liver samples and were typed into 3 serovars: S. ser. Schwarzengrund (78%), S. ser. Enteritidis (18%), and S. ser. Typhimurium 4(%). More than one Salmonella serovar was found in livers belonging to two chicken slaughterhouse companies. All strains were susceptible to all antibiotics tested, with the exception of erythromycin (100% resistant) and streptomycin (22% intermediate sensitivity). Overall, 32 (4.80%) and 3 (0.45%) of the chicken liver samples were positive for Salmonella sp. in preenrichment method and direct selective agar plating method, respectively; these percentages were significantly different (P = 0.0001; kappa = 0.16). There was also a statistical difference in relative accuracy, sensitivity and negative predictive value between the preenrichment method and the direct selective agar plating method; the first had greater values for these parameters than the direct selective agar plating method. These parameters were statistically different between MacConkey agar (MCA) and modified lysine iron (MLIA) in the two culture methods; the second had greater values than MCA for both culture methods. This study shows that even though serovars that are important for public health were isolated, the prevalence of Salmonella sp. is low in chicken livers from Entre Rios, Argentina. The isolated strains do not have multi-resistance patterns. Furthermore, the preenrichment method and MLIA are superior to the direct selective agar plating method and MCA for Salmonella sp. isolation from chicken liver samples, respectively.